2017
DOI: 10.18632/oncotarget.19037
|View full text |Cite
|
Sign up to set email alerts
|

DCK expression, a potential predictive biomarker in the adjuvant gemcitabine chemotherapy for biliary tract cancer after surgical resection: results from a phase II study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 29 publications
2
13
1
Order By: Relevance
“…In cancer chemotherapy, dCK is an enzyme needed for phosphorylation of several deoxyribonucleosides and their nucleoside analogs such as gemcitabine and cytarabine and is known as a rate limiting enzyme in activation of these drugs. Furthermore, in addition to a report that the deficiency of dCK is involved in resistance to gemcitabine and cytarabine, it has also been reported that these drugs show very high anti-tumor efficacy in cancer cells that overexpress dCK (14)(15)(16)(17). We found for the first time that the expression levels of dCK increase with the acquisition of resistance to cetuximabin this study.…”
Section: Discussionsupporting
confidence: 69%
“…In cancer chemotherapy, dCK is an enzyme needed for phosphorylation of several deoxyribonucleosides and their nucleoside analogs such as gemcitabine and cytarabine and is known as a rate limiting enzyme in activation of these drugs. Furthermore, in addition to a report that the deficiency of dCK is involved in resistance to gemcitabine and cytarabine, it has also been reported that these drugs show very high anti-tumor efficacy in cancer cells that overexpress dCK (14)(15)(16)(17). We found for the first time that the expression levels of dCK increase with the acquisition of resistance to cetuximabin this study.…”
Section: Discussionsupporting
confidence: 69%
“…32 In line with the essential roles of hENT1 and dCK in gemcitabine metabolism, the hENT1 knockdown in biliary tract cancer cells 20 and dCK knockdown in pancreatic cancer cells 19 attenuated cell sensitivity to gemcitabine, which is consistent with the present results. High expression levels of hENT1 or dCK were associated with better survival in gemcitabine-treated cholangiocarcinoma 20 , 21 and pancreatic cancer, 17 , 18 , 22 , 23 indicating that the functional roles of hENT1 and dCK in vitro reflect their roles in gemcitabine sensitivity in clinical settings. Therefore, the present results demonstrated that patients with meningiomas expressing high levels of hENT1 and dCK may benefit from gemcitabine-based chemotherapy and, thus, clinical trials to test the efficacy of gemcitabine in high-grade meningiomas are warranted.…”
Section: Discussionmentioning
confidence: 98%
“…Although the incidence of BTC is relatively low, the heavy disease burden is associated with poor survival outcome. Even if BTC is diagnosed at an early stage and curative resection is performed, a short recurrence-free survival (11–20 months) and a high recurrence rate (53–62%) have been reported in previous studies [ 2 5 ]. Furthermore, most patients are initially diagnosed with advanced stage hepatobiliary cancer [ 6 ].…”
Section: Introductionmentioning
confidence: 96%
“…Identifying indicators that can predict the survival outcome of patients with advanced hepatobiliary cancers will help practitioners provide optimal care and management of these patients. According to recent studies, Child-Pugh score, body mass index (BMI), and aspartate aminotransferase (AST) for HCC and Eastern Cooperative Oncology Group Performance Status (ECOG-PS), carcinoembryonic antigen, carbohydrate antigen 19–9, hemoglobin (Hb), white blood cell (WBC), and albumin for BTCs have been identified as potential prognostic biomarkers for predicting survival in advanced hepatobiliary cancers [ 2 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%